Virologic and Immunologic Responses in Patients on Highly Active Antiretroviral Active Therapy in Vhembe District, South Africa: A Retrospective Study - Aniekan, Adet (My University, 2017)
Background: South Africa presently has a very high HIV burden. It has adopted the UNAIDS “90-90-90 targets” to curb its HIV burden. This target aims to attain sustained viral suppression in 90% of all persons receiving antiretroviral therapy. This is supported by several studies. Studies to observe if patients are achieving and sustaining viral suppression in Limpopo, South Africa, are few. Objective: To investigate the viral and immunologic responses of patients in Vhembe District to highly active antiretroviral therapy (HAART) between the 1st of January 2004 and 31st of July 2016. Methodology: This was a retrospective medical record review conducted in Vhembe District in rural Limpopo. It included the medical records of 1247 individuals from Thohoyandou Community Health Centre. Analysis was done using SPSS 24.0. To model the factors associated with virologic and immunologic responses, each independent variable was tested for association with the dependent variable (viral suppression and CD4 count increase of ≥ 50 cells/μL from baseline to 6 months). The independent variables included age, year of initiation, gender, marital status, baseline BMI, haemoglobin, clinical stage and estimated creatinine clearance. The Pearson Chi square (X2) was used for all categorical independent variables and the t-test, for all continuous independent variables, to test for association. The estimate used was a 95% confidence interval, and a p-value of < 0.05 was considered significant. Results: The study showed that 52.6% of individuals were in clinical stage I at baseline. Viral suppression (viral load < 50 copies/ml) at 6 months was 64% (n = 648), 72% (n =193) at 60 months and 94% (n = 16) at 132 months. Fifty-nine percent had consistent viral suppression for a period of at least 6 months. Consistent viral suppression (viral load < 50 copies/ml on at least one consecutive occasion without any intervening viral load > 50 copies/ml) for at least 54 months was only 14%, while 2.3% had a delay in switching from a failing regimen. The mean CD4 count at baseline was 227 cells/μL, and 538 cells/μL at 60 months. The mean CD4 cell count increase from baseline to 6 months was 190 cells/μL. The immuno-virologic discordance was 27%. Patients with higher baseline CD4 count and females were significantly (p = 0.001 and 0.031 respectively) more likely to achieve viral suppression at 6 months. Those below 45 years and females were v significantly (p = 0.011 and 0.043 respectively) more likely to achieve adequate CD4 count increase at 6 months. Conclusions: The proportion of individuals with viral suppression in the District increased from 6 months onwards, and is fairly adequate. However, sustainability of viral suppression, once attained, is low. Adequate immunologic response, however, seems high. Males and age group above 45 years appear to have poorer responses to HAART.
MPH
Department of Public Health
Keywords: Virologic response; UCTD; Immunolologic response; Highly Active Antiretroviral Therapy; 616.97920968257; AIDS (Disease) -- Patients -- South Africa -- Limpopo; HIV-positive persons -- South Africa -- Limpopo; HIV infections -- South Africa -- Limpopo; AIDS (Disease) -- Prevention -- South Africa -- Limpopo; Antiviral agents -- South Africa -- Limpopo